Does one more or one less mobile operator affect prices? A comprehensive ex-post evaluation of entries and mergers in European mobile telecommunication markets - Gergely Csorba; Zoltán Pápai (Hungarian Academy of Sciences, Institute of Economics, 2015)
This paper estimates the impact of entries and mergers on the price of mobile voice services in a panel database of 27 European Member States between 2003 and 2010. Our difference-in-differences econometric methodology exploits the variance in different structural changes between countries to separate the respective effects. Our results show that the effect of entry crucially depends on the number of active operators and the type of entrant, and not controlling for these differences might lead to misleading conclusions. We find no robust evidence that entry has a price-decreasing effect on markets with originally 2 operators. However, the entry of a 4th operator does have a price-decreasing effect, but with different dynamics concerning the entrant's type. When we separate entry effects for the subsequent years, we show that the significant price-decreasing effects for local operators entering occur only in the first year after entry, while the price-decreasing effects for multinational entries are significantly larger on the long-run. Last, we find no price-increasing effects of 5-to-4 mergers, but a long run price-increasing effect of a 4-to-3 merger.
Keywords: L11; L49; L59; L96; 330; ex-post evaluation; mobile telecommunications; entry; merger; difference-in-differences estimations